NORMS OF SQUARE FREE IDEALS IN QUADRATIC FIELDS - et al., G SUDHAAMSH MOHAN REDDY (International Journal of Control and Automation, 2019)
Norms of square free ideals in a quadratic field are recognized to be cube free integers. The proportion of norms among cube free integers is estimated (in a finite interval)